Leadership in Integrated Islamic Public Private Schools in Rejang Lebong Regency - Hamengkubuwono Hamengkubuwono; M. Iqbal Liayong Pratama (Universitas Bengkulu, 2022)
In Rejang Lebong district there are many private schools, those private schools were originally very existent, had a reputation and became a part that was trusted by the community as a place for their children to study. Along with current developments, the emergence of integrated Islamic-based private schools is actually more favored by the community so that most of the other private schools have to close because they cannot compete. Through interviews and observations to managers and teachers at Islamic-based private schools integrated with a qualitative approach. The collected data is reduced, presented and analyzed. The conclusion obtained is that an integrated Islamic-based school in the Rejang Lebong district is one of the schools that has received the attention of the community so that many entrust their sons and daughters to become students at the institution. The success of this school is because in the process of leadership it carries out several strategies, namely exemplary, intensive school programs, continuous supervision, continuous improvement, good cooperation, continuous coordination, has school characteristics, has talent development programs, interests and creativity of students, focuses on service. customer satisfies a balance of cognitive, affective, and psychomotor domains.